2005
DOI: 10.1177/003804070507800201
|View full text |Cite
|
Sign up to set email alerts
|

From “Middle Class” to “Trailer Trash:” Teachers' Perceptions of White Students in a Predominately Minority School

Abstract: This article explores how teachers perceived and interacted with white students in a predominately racial/ethnic minority school in Texas. On the basis of ethnographic data, the author found that different teachers expressed different views of the family and class backgrounds of white students in this setting, which ranged from “middle class” to “trailer trash.” These views of social class stemmed from how teachers interpreted the whiteness of students in this predominately minority context and influenced how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 38 publications
0
56
1
Order By: Relevance
“…That is, teachers' perceptions of their students may change in schools where white students are not the majority. Morris's (2005) ethnography of a predominantly black school in Texas reported that white teachers often assumed the white students were from lower-socioeconomic-status or ''trailer trash'' families while the black teachers assumed the same students were middle class. Do teachers' views of black and white students differ in predominantly black schools?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, teachers' perceptions of their students may change in schools where white students are not the majority. Morris's (2005) ethnography of a predominantly black school in Texas reported that white teachers often assumed the white students were from lower-socioeconomic-status or ''trailer trash'' families while the black teachers assumed the same students were middle class. Do teachers' views of black and white students differ in predominantly black schools?…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions that whiteness corresponds to intelligence and giftedness have been reported in multiple ethnographies of high schools and elementary schools (Morris 2005;Staiger 2004;Tyson 2003). Table 3 presents odds ratios that indicate the tendency for nonwhite teachers and white teachers of nonwhite students to report evaluations of scholastic ability that differ from white teachers' views of their white students' abilities.…”
Section: Teachers' Evaluations Of Scholastic Abilitymentioning
confidence: 99%
“…Over time, these teens adopted a shared view of themselves as low achievers, trouble makers, and outsiders, resulting in further marginalization and alienation from mainstream institutions and social networks (cf. also Morris 2005).…”
Section: Stigma and Mobile Homes In Previous Researchmentioning
confidence: 99%
“…They are shaped by contingencies in daily life that are not easily recognized in the framework of whiteness studies. Individuals interpret these exchanges not just as a matter of race, but also as a matter of class, family, and place (Erdmans 2004;Levine-Rasky 2000;Lewis 2004;Hartigan 1999Hartigan , 2000aMaimi et al 2002;Morris 2005;Perera 1999). Classes have distinctive cultures that consist of values, attitudes, beliefs, and practices that reflect objective positions within the mode of production.…”
Section: Whither the Class Struggle?mentioning
confidence: 99%
“…These cultures construct meanings, organize perceptions, define priorities, and influence behaviors. They provide differing degrees of capital for adapting to, and taking advantage of, local circumstances (Garner 2006;Lareau 2003;Morris 2005;Levine-Rasky 2000;Rose 1997;Royster 2003). For example, white children who live in economically poor and isolated neighborhoods that lack appropriate resources are just as likely as their nonwhite counterparts in similar circumstances to adopt a frame of reference that encourages failure (Lew 2006).…”
Section: Whither the Class Struggle?mentioning
confidence: 99%